Study on the mycorrhizal structure of common plants and rhizosphere AMF diversity of different plant communities in Central Province, Mongolia - Tsetsegmaa, Munkhzul; Chao, Lumeng; Bao, Yuying (Proceedings of the Mongolian Academy of Sciences, 2023)
With the dual destruction cased by man-made activities and natural causes, the biodiversity and ecosystem function of the prairie are reducing rapidly, which are manifest in such phenomenon as grassland desertification, sharp reduction in wetland, soil quality degradation, erosion of soil by wind, rain and watersheds. This condition restricts the development level of Mongolia's financial status and production forces, and so the protection and utilization of biodiversity resources are extremely important and harbor no delay. Arbuscular mycorrhizal fungi (AMF) has a broad distribution and species diversity, it also has very important functions of maintaining material circulation in ecosystems, improving ecosystem productivity, and ensuring ecological restoration. We selected different plant communities and the common plants in the Tuv aimag (Central province) of Mongolia to study the correlation between species diversity, genetic diversity and AM fungi distribution with physical and chemical properties of soil.